2007
DOI: 10.1291/hypres.30.895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Long-Term Aerobic Exercise on Arterial Stiffness in the Elderly

Abstract: Arterial stiffness is an important factor for cardiovascular performance and a predictor of cardiovascular risk. We evaluated the effects of both acute and long-term aerobic exercise on arterial stiffness in community-dwelling healthy elderly subjects. In addition, we evaluated the relationship between the effects of longterm exercise and those of acute exercise. The study subjects were participants in the Shimanami Health Promoting Program study (J-SHIPP), which was designed to investigate factors relating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 42 publications
(48 reference statements)
4
40
0
1
Order By: Relevance
“…Several points may explain the discrepancy between the study of Tabara et al (12) and the previous reports (9,14,15). First, in two of the previous reports the study periods were 8 weeks (15) and 3 months (9), both of which were shorter than the 6-month aerobic training performed in the study of Tabara et al (12).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Several points may explain the discrepancy between the study of Tabara et al (12) and the previous reports (9,14,15). First, in two of the previous reports the study periods were 8 weeks (15) and 3 months (9), both of which were shorter than the 6-month aerobic training performed in the study of Tabara et al (12).…”
mentioning
confidence: 79%
“…Several points may explain the discrepancy between the study of Tabara et al (12) and the previous reports (9,14,15). First, in two of the previous reports the study periods were 8 weeks (15) and 3 months (9), both of which were shorter than the 6-month aerobic training performed in the study of Tabara et al (12). Second, the other previous study (14) examined the effects of combined aerobic and resistance training, and resistance training has been reported to have unfavorable effects on arterial stiffness (16).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The effect of acute exercise on AIx in offspring of hypertensive individuals has not been explored; however, Tabara et al 17 found that there was no change in AIx after acute exercise in apparently healthy and sedentary elderly subjects, although AIx changed after 6 months of aerobic exercise. Thus, it is undetermined what effect acute exercise would have on the AIx of young offspring of hypertensives.…”
Section: Introductionmentioning
confidence: 99%